The Synthesis of (±)‐Oxyisocyclointegrin. Issue 7 (25th January 2019) - Smith, Robert J.; Bower, Rebekah L.; Ferguson, Scott A.; Rosengren, Rhonda J.; Cook, Greg M.; Hawkins, Bill C.
Abstract : The total synthesis of oxyisocyclointegrin is described. The key steps in the synthesis included a Tsuji–Trost allyl migration to exclusively afford the corresponding monoallylated 1, 3‐diketone and a photochemical initiated oxidative cyclization to forge the oxepine core. Abstract : The total synthesis of the oxepine‐fused flavone natural product oxyisocyclointegrin is described. The synthesis was achieved in 7 steps and an overall yield of 15 %, oxyisocyclointegrin was found to possess moderate antibacterial activity and modest cytotoxicity.